A computational examination of the therapeutic advantages of fourth-generation ALK inhibitors TPX-0131 and repotrectinib over third-generation lorlatinib for NSCLC with ALK F1174C/L/V mutations - Balasundaram, Ambritha; Doss, George Priya C. (Frontiers in Molecular Biosciences, 2024)
Background: In non-small-cell lung cancer (NSCLC), a pivotal factor in promoting cancer development is the rearrangement in the anaplastic lymphoma kinase ALK gene, resulting in elevated ALK protein expression. F1174C/L/V is the acquired secondary resistant mutation in ALK. Significant survival improvements have been seen while tyrosine kinase inhibitors specifically target ALK. Nevertheless, the emergence of drug resistance hinders the clinical effectiveness of these drugs. Objective: This research sought to find the binding affinity/inhibitory effects of the existing drug lorlatinib (LOR) and upcoming TPX-0131 (zotizalkib/TPX) and repotrectinib (TPX-0005/REP) inhibitors against ALK F1174C/L/V mutations using computational approaches to identify potential strategies over resistance. Methods: We conducted molecular docking, molecular dynamics simulation, and MMPBSA calculations to investigate how compact macrocyclic inhibitors, such as TPX-0131 and repotrectinib, fit within the ATP-binding boundary and differ from LOR. Results: Our results demonstrated that TPX-0131 and repotrectinib contributed to higher binding energy in F1174C and F1174L mutations than LOR. Repotrectinib showed greater binding energy in the F1174V mutation, whereas LOR and TPX-0131 exhibited similar binding energy. However, all three inhibitors showed significant binding energy toward F1174C/L/V mutations found in NSCLC. Conclusion: This comparative study of the potential binding effects of fourth-generation inhibitors TPX-0131 and repotrectinib and third-generation inhibitor LOR for ALK F1174C/L/V mutations revealed the atomistic insights of the binding mechanism. These computational findings enable us to carry out further research for the clinical implementation of fourth-generation ALK inhibitors on ALK-positive NSCLC.